Social Ecology of Hypertension Management Among Latinos Living in the U.S.–Mexico Border Region. Issue 4 (July 2022) - Cacari Stone, Lisa; Sanchez, Victoria; Bruna, Sean Patrick; Muhammad, Michael; Zamora, MPH, Carmen
Introduction: While a growing body of research examines individual factors affecting the prevalence and management of hypertension among Latinos, less is known about how socioecological factors operate to determine health and affect implementation of interventions in rural communities. Method: We conducted eight focus groups to assess perceived risks and protective factors associated with managing hypertension among Latino adults and their family members living in two rural/frontier counties in the U.S.–Mexico border region. This analysis is part of a larger study, Corazon por la Vida (Heart for Life), which involved multiple data collection strategies to evaluate the effectiveness of a primary care and a promotora de salud intervention to manage hypertension. Results: Of the 49 focus group participants, 70% were female and 30% were male, 39% were Spanish-only speakers, and 84% had hypertension. Participants' ages ranged between 18 and 75 years, and 63% reported annual incomes below $30, 000. Drawing from a social–ecological framework to analyze focus group data, four major themes and subthemes emerged as factors facilitating or inhibiting disease management: (1) individual (emotional burdens, coping mechanisms), (2) social relationships (family as a source of support, family as a source of stress), (3) health system (trust/mistrust, patient–provider communication), and (4) environment (lack of access to safe exercise environment, lack of affordable food). Conclusion: Our findings are relevant to public health practitioners, researchers, and policymakers seeking to shift from individual level or single interventions aimed at improving treatment-modality adherence to multilevel or multiple interventions for rural Latino communities.